A new multi-scale structure finding algorithm to identify cosmological structure - Snedden, Ali; Phillips, Lara Arielle; Mathews, Grant J.; Coughlin, Jared; Suh, In-Saeng; Bhattacharya, Aparna (Journal of computational physics, 2015)
We introduce a new structure finding algorithm that self-consistently parses large scale cosmological structure into clusters, filaments and voids. This structure finding algorithm probes the structure at multiple scales and classifies the appropriate regions with the most probable structure type and size. We show that it can identify the baryon fraction of intercluster medium and cosmological voids.